Hunted and Honoured: Animal Representations in Precontact Masks from the Nunalleq Site, Southwest Alaska - Mossolova, Anna; Knecht, Rick; Masson-MacLean, Edouard; Houmard, Claire (Études Inuit Studies, 2019)
The precontact lifeways of Yup’ik people in Southwest Alaska were poorly known until the 2009–2018 excavations at the Nunalleq site near the village of Quinhagak. Until recently, the site dating from around AD 1400–1675 had been locked in permafrost that secured the extraordinary preservation of organic artefacts and faunal materials. As in many other hunter-gatherer communities across the North, animals were economically and culturally central to the lives of Nunalleq residents. This multidisciplinary paper combines the ethnographic study of unearthed artefacts with the results of subsistence and dietary studies at Nunalleq, and demonstrates how precontact Yup’ik ecologies were embodied in material culture, particularly in the iconography of ceremonial objects such as masks and mask attachments. Early ethnographic records and collections suggest that Yup’ik masks were often complex in structure and imagery, and can be considered miniature models of a multilayered and ensouled universe. Masks and other material culture representations highlight the way humans and animals are related and ontologically linked in Yup’ik worldviews. By taking this approach, this study aims to better understand the role of animals in the belief systems and lifeways of a precontact Nunalleq community.